Resilience as a psychiatric factor affecting outcomes after total joint arthroplasty: a systematic review - Andrew G. Kim; Parshva Sanghvi; Adam A. Rizk; Aaron Ahn; Thomas J. Pumo; Atul F. Kamath (Arthroplasty, 2024)
Abstract Introduction Mental and psychiatric status continue to be underscreened prior to total joint arthroplasty (TJA). Research on the role of resilience as a psychiatric factor affecting TJA outcomes remains limited. Therefore, our systematic review sought to evaluate the impact of patient resilience in TJA. Methods A systematic review of the literature from the Pubmed, MEDLINE, EBSCOhost, and Google Scholar online databases was performed in abidance with Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. Studies reporting on outcomes following primary total hip arthroplasty (THA) and/or total knee arthroplasty (TKA) segregated by patient resilience were included. Case reports, reviews, meta-analyses, and conference abstracts were excluded. Primary outcomes of interest included patient-reported outcomes (PROs), surgical outcomes, and postoperative opioid consumption. Results Twelve articles were included reporting on a total of 1,577 TJAs. There was a strong agreement that the Patient Reported Outcomes Measurement Information System (PROMIS)-Physical Health and Mental Health components were strongly predicted by patient resilience. However, there was inconclusive evidence regarding the impact of resilience on UCLA Activity Scales (UCLA) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) outcomes as well as postoperative hip and knee function. Similarly, conflicting evidence was presented regarding the effect of resilience on length of stay (LOS). Greater resilience was associated with reduced opioid usage in the immediate inpatient postoperative period. However, resilience had no significant effect on opioid requirements in the postoperative outpatient follow-up time frame. Conclusion The present analysis demonstrated mixed, inconclusive evidence regarding the impact of resilience on postoperative outcomes. The paucity of research evaluating this relationship warrants further investigation, examining both short and long-term outcomes. Due to the limited literature evaluating resilience as a predictor of outcomes following TJA, we cannot definitively rule out resilience as a valuable metric and must further examine its utility as a preoperative screening tool. Level of evidence III.